Environmental and senescent related variations in Weddell seal body mass: implications for age-specific reproductive performance - Proffitt, KM; Garrott, RA; Rotella, JJ; Wheatley, KE (2007)
Recent studies have found age-specific variations in reproductive performance amongst Weddell seals, Leptonychotes weddellii, and we hypothesized age-related variations in maternal body mass as a mechanism linking maternal age and the observed patterns of reproductive performance. We evaluated the effects of maternal traits such as age and reproductive experience and the effects of environmental variations on maternal body mass at parturition. Maternal body mass at parturition showed substantial age- and environmental-related variations. Maternal body mass increased with age through the young and middle ages, and evidence of senescent declines in body mass was found amongst the oldest ages. Additionally, body mass at parturition was strongly influenced by environmental variations during the pregnancy period, specifically sea-ice extent and the state of the El-NiÃ±o Southern Oscillation. Patterns of age-specific variations in body mass were consistent with age-specific patterns of offspring survival probability, which supported our hypothesis that changes in body mass link maternal age and reproductive performance in the Weddell seal. Further, environmental conditions during pregnancy may be an important component of Weddell seal reproductive performance. Â© OIKOS.